(untitled) (Nexus International Journal of Science and Education, 2024)
This study explored the performance tasks of secondary students in Technology and Livelihood Education as narrated by the teachers. There were eight (8) TLE teachers who participated in the study coming from Kapalong East District, Davao del Norte. This study made use of a phenomenological approach to extract the ideas of the teacher participants. The in-depth-interview was employed to gather some information as regards to their respective experiences. Using the thematic analysis, the following themes emerged as pertains to the experiences of the participants: the experiences of the TLE teachers revealed three themes such as: Increased self-esteem, Heightened motivation and Low student involvement. The coping mechanisms of the teachers were Encouraging full activity participation, strengthening class teamwork and inspiring actual class demonstration. The educational management insights were focused on two factors: Keeping track on students’ skills and Creating group circles. For the principals or school heads to be more sensitive to the needs of the teachers and the students. The curricular offering in TLE classes were more complex as compared to other courses in the curriculum. The TLE teachers may be more observant on their actions and classwork activities. They may look into the individual needs of their students. The teachers may also acknowledge the students’ performances and help the students who are not inclined to the area of home economics.